A Persistently Increasing Precipitation Trend Through the Holocene in Northwest China Recorded by Black Carbon δ13C From Sayram Lake - Jiang, Qingfeng; Zheng, Jianan; Yang, Yufeng; Zhao, Wenwei; Ning, Dongliang (Frontiers in Earth Science, 2020)
Precipitation is the crucial factor for the stability and sustainable development of ecosystem and human community in arid areas under the future climate change.However, Holocene precipitation evolution and its long-term characters in arid northwest China have not been well documented. Thus, more reconstruction records are needed to deepen our understanding of the regional Holocene precipitation variation.In this study, we present a well-dated and high-resolution black carbon isotope-inferred precipitation record over the last 12880 cal.yr BP from Sayram Lake in the western Tianshan Mountains, Xinjiang province, northwest China. The variation of the black carbon δ 13 C values indicate that the precipitation in the study areas gradually decreased from ~12280 to 9260 cal.yr BP, and then persistent increased after 9260 cal.yr BP to the present with millennial to centennial timescale oscillations superimposed on this general trend. During the Holocene, a distinct less precipitation stage appeared in 9800-8800 cal.yr BP and two episodes of increasing precipitations occurred in 8000-7600cal.yr BP and 5800-2500 cal.yr BP respectively, with the highest rainfall around at ~3800 cal.yr BP. The precipitation persistent increasing trend is generally consistent with the records from surrounding areas. Solar radiation and its activities on the millennial and centennial timescales control the precipitation variation in the arid Northwest China through the influence on the North Atlantic SST and westerly wind intensity to determine the water vapor transported to Xinjiang. Our study results will facilitate the understanding on the driving mechanisms of Holocene precipitation evolution.